Analisis Faktor-Faktor yang Berhubungan dengan Kinerja Petugas Kesehatan di Puskesmas Kota Soe Kabupaten TTS Tahun 2023 - Wantrimin Yulianti Tuanane; Rina Waty Sirait; Masrida Sinaga (Yayasan Literasi Sains Indonesia, 2024)
Health workers are required to have the ability and skills to work in order to produce good performance, thus providing quality health services. The minimum service standards have not been achieved at the Kota Soe Health Center mean that the performance of health workers is not optimal. Performance is influenced by various factors, from motivational factors, work environment, rewards, and work discipline. The purpose of this study was to determine the factors associated with the performance of health workers at the Kota Soe Health Center in 2023. This research is an analytic survey research with cross sectional approach. The sample in this study consisted of 45 people with a sampling technique that is simple random sampling. Data collection used questionnaires, data analysis was carried out univariate and bivariate, then tested using the chi square statistical test. The results showed that there was a relationship between motivation and the performance of health workers with a value (p=0.025), there was a relationship between the work environment and the performance of health workers with a value (p=0.001), there was a relationship between appreciation and the performance of health workers with a value (p=0.004), and there was a relationship between work discipline and the performance of health workers with a value (p=0.001). It is expected that Health workers need to pay attention to health facilities again, organize the work environment properly, improve the distribution of incentives, leader can appreciate the work of health workers, and affirm time discipline.